Long-term effects of linear versus macrocyclic GBCAs on gene expression in the central nervous system of mice - Chuanbing Wang; Yuxia Tang; Jiajia Tang; Jie Zhang; Siqi Wang; Feiyun Wu; Shouju Wang (European Radiology Experimental)
Abstract Background We examined chronic gadolinium retention impact on gene expression in the mouse central nervous system (CNS) after injection of linear or macrocyclic gadolinium-based contrast agents (GBCAs). Methods From 05/2022 to 07/2023, 36 female mice underwent weekly intraperitoneal injections of gadodiamide (2.5 mmol/kg, linear), gadobutrol (2.5 mmol/kg, macrocyclic), or saline. Mice were sacrificed on day 29 or 391 after a 1-year washout. Assessments included magnetic resonance imaging (MRI), mechanical hyperalgesia tests, and inductively coupled plasma mass spectrometry to measure gadolinium levels. Ribonucleic acid (RNA) sequencing and bioinformatic analyses identified differentially expressed genes (DEGs), with validation by quantitative reverse transcription polymerase chain reaction (qRT-PCR) and western blot (WB). Results Post-gadodiamide, MRI showed increased signal intensity in the deep cerebellar nuclei (pre, 0.997 ± 0.006 versus post, 1.086 ± 0.013, p < 0.001). Mechanical hyperalgesia tests indicated transient sensory changes. After 1-year, gadolinium retention was noted in the brain (5.92 ± 0.32 nmol/kg) and spinal cord (1.23 ± 0.66 nmol/kg) with gadodiamide, compared to saline controls (0.06 ± 0.02 nmol/kg in brains and 0.28 ± 0.06 nmol/kg in spinal cords). RNA sequencing identified 17 shared DEGs between brain and spinal cord in the gadodiamide group on day 391, with altered Hmgb2 and Sgk1 expression confirmed by qRT-PCR and WB. Reactome pathway analysis showed enrichment in neuroinflammation pathways. No DEGs were detected in brains on day 29. Conclusion Chronic gadolinium deposition from repeated linear GBCA but not macrocyclic administration causes significant gene expression alterations in the mouse CNS, particularly affecting neuroinflammation pathways. Relevance statement This study examined the long-term impact of chronic gadolinium retention on gene expression in the mouse CNS, uncovering significant changes associated with neuroinflammation pathways after repeated administration of linear GBCA, but not with macrocyclic GBCA. These findings highlight the importance of further research on the long-term safety of linear GBCA in medical imaging. Key Points Chronic gadolinium retention alters gene expression in the mouse central nervous system. Significant neuroinflammatory pathway changes were observed after linear gadodiamide exposure. MRI showed increased signal intensity in deep cerebellar nuclei after gadodiamide injection. Graphical Abstract